Optimizing Trademark Protection for Global Competitiveness: Comparative Study of Indonesia and ASEAN - Winarno; Suyoto; Aloysius Wisnubroto (Fakultas Hukum Universitas Islam Indonesia, 2026)
This study examines the optimization of trademark protection in Indonesia within the context of global business competition and regional integration under the ASEAN Economic Community (AEC). As a key component of intellectual property rights (IPR), trademarks play a crucial role in supporting business competitiveness and consumer trust. However, ASEAN countries exhibit significant differences in their legal frameworks, enforcement mechanisms, and institutional capacities. This research applies a comparative legal approach to analyze the similarities and differences between Indonesia and other ASEAN member states. The findings reveal that while all ASEAN countries adhere to the TRIPS Agreement and adopt the first-to-file system, disparities persist in enforcement, administrative efficiency, and public awareness. Strengthening legal certainty and cross-border cooperation is essential to improve Indonesia’s competitiveness and align its trademark regime with international best practices.